A linear program for optimizing enhanced weathering networks - Tan, Raymond Girard R. (Animo Repository, 2019)
We develop a linear programming (LP) model for optimizing enhanced weathering (EW) networks. EW is a negative emissions technology (NET) that involves mining and grinding of naturally occurring CO2-reactive rocks, and subsequently applying the resulting powder to soil to provide ample surface area for contact with the atmosphere and thus accelerate carbon fixation. Use of EW as a carbon management strategy at scale will result in the need to properly match sources (rock crushing plants) with sinks (application sites); the result is a special case of a supply chain optimization problem. The model proposed here can determine optimal matches of sources and sinks in EW-based CMNs, considering material flow and temporal constraints. A case study is solved to illustrate the model. © 2019